2022
DOI: 10.1017/s0031182022000531
|View full text |Cite
|
Sign up to set email alerts
|

Context-dependent parasite infection affects trophic niche in populations of sympatric stickleback species

Abstract: How parasites alter host feeding ecology remains elusive in natural populations. A powerful approach to investigate the link between infection and feeding ecology is quantifying unique and shared responses to parasite infection in related host species within a common environment. Here, 9 pairs of sympatric populations of the three-spined and nine-spined stickleback fishes were sampled across a range of freshwater and brackish habitats to investigate how parasites alter host feeding ecology: (i) biotic and abio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…This was also confirmed by the higher number of ASVs in the nine-spined stickleback ( Figure 2 ). Higher microbial diversity suggests broader niche use in the nine-spined stickleback, which is consistent with the observation that nine-spined stickleback occupies a slightly higher trophic position ( Thorburn et al, 2022 ). A comparable study by Fietz et al (2018) observed a similar alpha diversity pattern in sand lance fishes ( Ammodytes tobianus and Hyperoplus lanceolatus ) from the Baltic Sea, with higher alpha diversity in A. tobianus .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This was also confirmed by the higher number of ASVs in the nine-spined stickleback ( Figure 2 ). Higher microbial diversity suggests broader niche use in the nine-spined stickleback, which is consistent with the observation that nine-spined stickleback occupies a slightly higher trophic position ( Thorburn et al, 2022 ). A comparable study by Fietz et al (2018) observed a similar alpha diversity pattern in sand lance fishes ( Ammodytes tobianus and Hyperoplus lanceolatus ) from the Baltic Sea, with higher alpha diversity in A. tobianus .…”
Section: Discussionsupporting
confidence: 88%
“…The three-spined stickleback ( Gasterosteus aculeatus Linnaeus, 1758) and the nine-spined stickleback ( Pungitius pungitius Linnaeus, 1758) are important model organisms for the study of natural selection and adaptive evolution ( Gibson, 2005 ; Raeymaekers et al, 2005 ; DeFaveri et al, 2012 ; Feulner et al, 2013 ; Merilä, 2013 ; Fang et al, 2021 ). Both species diverged around 26 million years ago ( Varadharajan et al, 2019 ), but have overlapping habitat requirements ( Zander, 1990 ), diet preferences ( Hart, 2003 ) and parasite communities ( Raeymaekers et al, 2008 ; Thorburn et al, 2022 ). Studies in three-spined stickleback have identified several environmental and host-specific factors that correlate with the diversity and community structure of the gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, trophic niche use at the study sites showed different trends for infected and uninfected cohorts among chub populations. This suggests that parasite infection on niche specialization is context‐dependent (Thorburn et al ., 2022). There is mounting evidence that stress factors, other than parasite infection, can alter physiological performance and affect the interindividual variability of the isotopic signature (Karlson et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%